Exploring Students’ Intention to Use LINE for Academic Purposes Based on Technology Acceptance Model - Van De Bogart, Willard; Wichadee, Saovapa (International Review of Research in Open and Distributed Learning, 2015)
The LINE application is often conceived as purely social space; however, the authors of this paper wanted to determine if it could be used for academic purposes. In this study, we examined how undergraduate students accepted LINE in terms of using it for classroom-related activities (e.g., submit homework, follow up course information queries, download materials) and explored the factors that might affect their intention to use it. Data were collected from 144 undergraduate students enrolled in an English course that utilized some activities based on LINE app using a questionnaire developed from TAM. Data were analyzed to see if relationships existed among factors when LINE was used to organize classroom experiences. The findings revealed that perceived usefulness and attitude toward usage had positive relationships with intention to use while perceived ease of use was positively related to perceived usefulness. In contrast with TAM assertions, this study did not find any relationship between perceived ease of use and attitude toward usage. Also, the number of social networking sites that students are using had no relationship with intention to use. The study also suggested some kinds of LINE-based learning activities preferred by students, which would be proposed for future courses. This study revealed several useful implications that TAM can be employed as a useful theoretical framework to predict and understand users’ intention to use new technologies in education.